Understanding Tensor Processing Units : The Specialized Hardware Revolutionizing AI Computing - Nikhila Pothukuchi (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
Tensor Processing Units (TPUs) represent a revolutionary advancement in specialized hardware architecture designed specifically for artificial intelligence workloads. This comprehensive article explores how TPUs have transformed the landscape of machine learning through their innovative systolic array architecture, optimized memory systems, and cloud-based accessibility. The article examines TPUs’ significant advantages in energy efficiency, training acceleration, and scalability across various AI domains, including natural language processing, computer vision, and recommendation systems. The article also investigates the democratization of AI computing through cloud platforms and discusses future implications for hardware evolution and industry impact, highlighting how TPU innovations are shaping the future of AI infrastructure and computational capabilities.